Legal interpreting in Montenegro in view of its EU accession: diagnosis and proposals of necessary modifications - Andjelic, Jasmina Tatar (MonTi Monografías de Traducción e Interpretación, 2016)
The aim of this paper is to analyze the current situation in the field of court interpreting in Montenegro, from both a normative and a practical point of view, in the light of future EU accession. Following the assertion that there is an increasing need for quality interpretation and the description of an ideal court interpreter, this paper presents the situation at the national level, relying upon the existing legislation in force. It is noted that Montenegrin legislation is generally harmonized with the EU Directive 2010/64/EU, but there is an issue of terminology that results in an unclear distinction between interpretation and translation. This paper proposes several solutions in order to define more detailed criteria for the selection of interpreters, form and content of the exam, necessity of organizing specialized training, introduction of a reliable system of quality control and establishment of a representative professional association.